2010
DOI: 10.1177/193229681000400608
|View full text |Cite
|
Sign up to set email alerts
|

Models of Glucagon Secretion, Their Application to the Analysis of the Defects in Glucagon Counterregulation and Potential Extension to Approximate Glucagon Action

Abstract: Abbreviations: (BG) blood glucose, (GABA) γ-aminobutyric acid, (GCR) glucagon counterregulation, (GLP-1) glucagon-like peptide-1, (HGO) hepatic glucose output, (ID 50 AbstractThis review analyzes an interdisciplinary approach to the pancreatic endocrine network-like relationships that control glucagon secretion and glucagon counterregulation (GCR). Using in silico studies, we show that a pancreatic feedback network that brings together several explicit interactions between islet peptides and blood glucose r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(36 citation statements)
references
References 77 publications
0
34
2
Order By: Relevance
“…We have also shown that the MCN could account for the observed in vivo pulsatile GCR response to hypoglycaemia triggered by switch‐off signals in insulin deficiency as detailed in figure 2 in Ref. [27] (see also Ref. [21]).…”
Section: In Silico Analysis Of the Glucagon Control Networkmentioning
confidence: 66%
See 1 more Smart Citation
“…We have also shown that the MCN could account for the observed in vivo pulsatile GCR response to hypoglycaemia triggered by switch‐off signals in insulin deficiency as detailed in figure 2 in Ref. [27] (see also Ref. [21]).…”
Section: In Silico Analysis Of the Glucagon Control Networkmentioning
confidence: 66%
“…Using our MCN model we simulated the response to hypoglycaemia assuming different strategies of glucagon reduction: gradual suppression of AFI or AFR glucagon, or both. Reduction in AFI glucagon improved (figure 4[27], top curve), while reduction in AFR secretion reduced the GCR (figure 4[27], lower curve). However, if inhibition of both AFI and AFR glucagon is assumed (as expected during an ACI infusion) the model predicts initial GCR enhancement followed by GCR gradual decline (figure 4[27], middle curve).…”
Section: Optimizing Glucagon Suppression To Repair Defective Gcrmentioning
confidence: 99%
“…There are promising animal data, but as yet no convincing proof in humans that this may occur. 73,74 …”
Section: Clinical Determination Of Risk Factors For Hypoglycemiamentioning
confidence: 99%
“…[112][113][114][115][116] Their complex behaviors, however, may not obviously be addressed by probing α-, β-and δ-cells separately. Even if they are not physically connected with each other, they communicate with each other via paracrine interactions which are mediated by hormones [117][118][119][120] or neurotransmitters.…”
Section: Paracrine Interactions Among Islet Cellsmentioning
confidence: 99%
“…On the other hand, the role of δ-cells is not fully known although there are reports that somatostatin secreted from δ-cells inhibits both α and β-cells. [127][128][129][130] In conclusion, despite both theoretical and experimental efforts as to the questions over the past 30 y, [112][113][114][115][116]127,128,131 there still lacks concrete understanding of the roles of the paracrine interactions among islet cells in glucose homeostasis. A variety of complicated interactions in an islet makes it difficult to recognize their roles, and existing experiments have focused mostly on static responses of the endocrine cells.…”
mentioning
confidence: 99%